2014
DOI: 10.1155/2014/131709
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Cardiometabolic Control in Type 2 Diabetes according to Gender and the Presence of Cardiovascular Disease: Results from the eControl Study

Abstract: The objective of this cross-sectional study was to assess differences in the control and treatment of modifiable cardiovascular risk factors (CVRF: HbA1c, blood pressure [BP], LDL-cholesterol, body mass index, and smoking habit) according to gender and the presence of cardiovascular disease (CVD) in patients with type 2 diabetes mellitus (T2DM) in Catalonia, Spain. The study included available data from electronic medical records for a total of 286,791 patients. After controlling for sex, age, diabetes duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
7
29
0
1
Order By: Relevance
“…The results of the present large-scale study showed that the TC and LDL-c levels were higher in women with T2DM than in men with T2DM, a finding consistent with those of previous studies [6, 17]. By studying patients with T2DM from 236 diabetes centers in Italy, Russo et al found that, compared to men, women had higher levels of TC, HDL-c, and LDL-c, were older, and had diabetes for a longer duration; further, more women than men failed to achieve the control goal of LDL-c levels [17].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the present large-scale study showed that the TC and LDL-c levels were higher in women with T2DM than in men with T2DM, a finding consistent with those of previous studies [6, 17]. By studying patients with T2DM from 236 diabetes centers in Italy, Russo et al found that, compared to men, women had higher levels of TC, HDL-c, and LDL-c, were older, and had diabetes for a longer duration; further, more women than men failed to achieve the control goal of LDL-c levels [17].…”
Section: Discussionsupporting
confidence: 93%
“…By studying patients with T2DM from 236 diabetes centers in Italy, Russo et al found that, compared to men, women had higher levels of TC, HDL-c, and LDL-c, were older, and had diabetes for a longer duration; further, more women than men failed to achieve the control goal of LDL-c levels [17]. Similarly, the eControl Study showed that, in the overall Spanish population, although the proportion of women on lipid-lowering therapy was slightly higher than that of men, the LDL-c levels in women were significantly higher than those in men; thus, irrespective of whether they have CVD as a complication, it is more difficult for women with T2DM to achieve the control goals of BMI and LDL-c level than it is for men [6]. The differences in the TC and LDL-c levels between genders may be related to differences in the pattern of changes of TC and LDL-c levels with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cohort of high-risk veterans, including 23,955 men and 1,010 women, LDL-C values were higher in women than men, with age-adjusted estimated mean values of 111.7 vs. 97.6 mg/dL (p < .01) [35]. A Spanish study, which included available data from electronic medical records for a total of 286,791 patients, reported although the proportion of women treated with lipidlowering medications was similar to (with prior CVD) or even higher (without CVD) than men, LDL-cholesterol levels were remarkably uncontrolled in both women with and women without CVD [36]. A Chinese study explored the reasons for the disparity in the lipid-lowering treatment goal attainment rates between women and men, and concluded that nearly half of the sex/gender disparity in lipid-lowering treatment goal attainment rates can be explained by the sex/gender differences in baseline lipid levels, socioeconomic status, cardiovascular comorbidities and associated risk factors, and the dosage of statin in high and very high CVD risk patients; however, the other half of the sex/gender disparity remains unexplained and requires further study to fully understand what other factors are at play [37].…”
Section: Sex/gender Disparities In Diabetes Carementioning
confidence: 99%